Intention To Visit The Executive Polyclinic Of The Dr. Sitanala Central General Hospital: A Review Of The Theory Of Planned Behavior - Rischa Zahra Bellanisa; Rina Anindita; Hosizah Hosizah (Pusat Riset dan Inovasi Nasional, 2024)
Executive polyclinic in the hospital provides premium health services for middle to upper-socioeconomic patients. However, the low utilization of executive polyclinic services is a concern for hospital management. This study uses the Theory of Planned Behavior framework to understand the factors that influence patient intention to visit the executive polyclinic. This study aims to analyze the effect of subjective norms and brand image on visiting intentions through attitudes toward visiting the Executive Polyclinic of dr. Sitanala Central General Hospital. The quantitative causal research method is to determine the relationship between variables based on previous hypotheses. Data were collected through questionnaires from 135 patients and visitors who had never visited the Executive Polyclinic of dr. Sitanala Central General Hospital was selected using Stratified Random Sampling. The analysis was carried out using SEM-PLS. The results showed that subjective norms and brand image influenced visiting attitudes and visiting intentions, and visiting attitudes influenced visiting intentions. In addition, attitudes mediate the influence of subjective norms on visiting intentions and brand image on visiting intentions. In a managerial context, this research can be a basis and reference for hospital management to improve communication and information systems, human resource (HR) management for medical personnel, patient experience management systems, and patient education systems.